Accuracy of standard test of renal function status IKA-1984 - Lydia Kosnadi, Lydia Kosnadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Measurements of standard inulin clearance and endogeous creatinine clearances were performed simultaneously in 112 children aged 2-14 years suffering from renal diseases. To diagnose the status of these renal functions, normal or decreased, a standard renal function test, namely IKA-1984, was used. The aim of this study was to investigate the accuracy of IKA-1984 compared with the other four standard renal function tests (i.e. Schwartz-1976, Feld-1990, Barratt-1975 and Chantler-1976). The data analysis used was clinical agreement in the interpretation of diagnostic tests. The results revealed very high kappa indexes (>0,80), providing IKA-1984 was accurate.Key words : inulin and creatinine clearances - renal function tests - accuracy - clinical disagreement - kappa index